DETERMINATION OF TOTAL PHENOLIC CONTENT AND ANTIOXIDANT ACTIVITY IN METHANOLIC EXTRACT OF ROBUSTA AND ARABICA COFFEE LEAVES - Nia Kristiningrum; Yeni Nur Cahyanti; Lestyo Wulandari (UNEJ e-Proceeding)
Phenols contained in coffee beans may also found inthe coffee leaves. Previous research showed that thearabica coffee leaves contain phenolic compounds[1]. Phenolic compounds are compounds that haveone or more hydroxyl groups attached directly to anaromatic ring [2]. Phenolics compounds have manybiological effects, including antioxidant activity [3].Antioxidants are the first line for defense againstfree radical damage, and important for health. Theneed for antioxidants becomes even more criticalwith increased exposure to free radicals. Pollution,cigarette smoke, drugs, illness, stress, and evenexercise can increase free radical exposure [4].The aim of this study was to determine totalphenolic content and antioxidant activity inmethanolic extracts of robusta and arabica coffeeleaves (old and young leaves), as potential sources ofnatural antioxidants. The relationship betweenphenolic content and antioxidant activity was alsoinvestigated.